2005
DOI: 10.1007/s11205-004-6169-5
|View full text |Cite
|
Sign up to set email alerts
|

Health And Quality Of Life Of Aboriginal Residential School Survivors, Bella Coola Valley, 2001

Abstract: Aboriginal health, comparative analysis design, inequality, residential schooling, quality of life,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 8 publications
2
13
0
1
Order By: Relevance
“…The results showed that 28.5% of respondents had attended a residential school. These data are consistent with other studies (e.g., Barton et al, 2005;First Nations Centre, 2005). The proportion of individuals who have attended residential schools increased with age, which is also consistent with the literature (Reading & Elias, 1999;First Nations Centre, 2005).…”
Section: Discussionsupporting
confidence: 94%
“…The results showed that 28.5% of respondents had attended a residential school. These data are consistent with other studies (e.g., Barton et al, 2005;First Nations Centre, 2005). The proportion of individuals who have attended residential schools increased with age, which is also consistent with the literature (Reading & Elias, 1999;First Nations Centre, 2005).…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, no differences were found in terms of levels of happiness, quality of life, and quality of relationships with family members between Aboriginals who had and had not gone to residential schools (Barton et al, 2005). No associations were also found between boarding school attendance and mental disorders in a sample of American Indian/Alaska Native women in primary care (Duran et al, 2004) or with lifetime alcohol dependence in a Navajo sample (Henderson, Kunitz, Gabriel, McCright, & Levy, 1998).…”
Section: Correlates Of Suicidality 11mentioning
confidence: 79%
“…Alcohol and drug use, suicide and suicidality, poorer perceived quality of life, and several mental disorders (e.g., depression, posttraumatic stress disorder) are more common in indigenous peoples than in non-indigenous samples (Allard, Wilkins, & Berthelot, 2004;Barton, Thommasen, Tallio, Zhang, & Michalos, 2005;Beals et al, 2005;Clarke, Colantonio, Rhodes, & Escobar, 2008;Compton, Thomas, Stinson, & Grant, 2007;Hasin, Goodwin, Stinson, & Grant, 2005;Hasin, Stinson, Ogburn, & Grant, 2007;Kinzie et al, 1992;Kirmayer, Brass, & Tait, 2000;Michalos, Thommasen, Read, Anderson, & Zumbo, 2005;Robin, Chester, Rasmussen, Jaranson, & Goldman, 1997a). The need for prevention and intervention strategies that are more conducive to the traditional culture and spirituality of indigenous peoples has been recognized by indigenous organizations and several researchers (e.g., Beals et al, 2005;Goldston et al, 2008;Health Canada, 2003;Katz et al, 2006).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Aboriginal and non-Aboriginal scholars agree that the relationship between the cumulative effects of historical trauma and current trauma, including sexual abuse, are directly related to the HIV epidemic among Indigenous peoples in North America (Barton, Harvey, Thommasen, Zhang, & Michalos, 2005;Braitstein et al, 2003;Duran, Duran, Yellow Horse Brave Heart, & Yellow Horse-Davis, 1998;Robin, Chester, Rasmussen, Jaranson, & Goldman, 1997a;Wesley-Esquimaux & Smolewski, 2004). We found significant univariate associations between having at least one parent who attended residential school and involvement in the child welfare system with sexual abuse among Cedar Project participants.…”
Section: Discussion Prevalence Of Sexual Abusementioning
confidence: 99%